Optical Signatures of Dissolved Organic Matter Transformation in the Global Ocean - Nelson, Norman B.; Gauglitz, Julia M. (Frontiers in Marine Science, 2016)
Characterization of dissolved organic matter in terms of its composition and optical properties, with an eye toward ultimately understanding its deep ocean dynamics, is the currently active frontier in DOM research. We used UV-visible absorption spectroscopy and fluorescence excitation-emission matrix (EEM) spectroscopy to characterize dissolved organic matter in the open ocean along sections of the U.S. CO2/CLIVAR Repeat Hydrography Project located in all the major ocean basins outside the Arctic. Despite large differences in fluorescence intensity between ocean basins, some variability patterns were similar throughout the global ocean, suggesting similar processes controlling the composition of the DOM. We find that commercially available single channel CDOM sensors are sensitive to the fluorescence of humic materials in the deep ocean and thermocline but not to the UVA-fluorescing and absorbing materials that characterize freshly produced CDOM in surface waters, revealing fundamental diversity in the DOM profile. In surface waters, UVA fluorescence and absorption signatures indicate the presence of freshly produced material and the process of bleaching removal, but in the upper mesopelagic and in the main thermocline these optical signatures are replaced by those of humic materials, with distribution patterns correlated to apparent oxygen utilization and other signatures of remineralization. Empirical orthogonal analysis (EOF) of the EEM data suggests the presence of two (unidentified) processes which convert “fresh” DOM to humic materials: one located in the surface ocean (shallower than 500m) and one located in the main thermocline. These hypothetical humification processes represent less than 5% of the overall variability in oceanic humic DOM fluorescence, which appears to be dominated by terrestrial input and solar bleaching of humic materials.